A Comparative Analysis of Patient Recovery and Complication Rates through Enhanced Surgical and Anesthetic Approaches in Orthopedic and General Surgery - Abdul Kaleem, Abdul Sami Mirani, Aneeta Kumari, Khadija, Ehsan Ullah Malik, Muhammad Khurram Zia, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives: This study aimed to compare perioperative outcomes, complication rates, and cost-effectiveness between enhanced and conventional surgical and anesthetic techniques in orthopedic and general surgery. The objective was to evaluate postoperative recovery, pain management, complications, and healthcare costs to optimize surgical care. Methodology: A comparative study was conducted at tertiary care hospitals in Sindh, Pakistan, following STROBE guidelines. Patients undergoing orthopedic and general surgery were categorized into four groups based on conventional or enhanced surgical and anesthetic techniques. Data on demographics, surgical parameters, anesthesia type, recovery metrics, and complications were collected through medical record reviews and standardized postoperative assessments at 1, 7, 30, and 90 days. Statistical analysis included multivariable logistic regression, t-tests, and chi-square tests, with significance set at p < 0.05. Results: Enhanced techniques significantly reduced surgical duration (orthopedic: 112 ± 25 to 98 ± 20 min; general: 130 ± 30 to 110 ± 22 min) and intraoperative blood loss (orthopedic: 410 ± 85 to 290 ± 70 mL; general: 520 ± 95 to 310 ± 75 mL). Hospital stay decreased (orthopedic: 6.8 ± 1.2 to 4.5 ± 0.8 days; general: 7.4 ± 1.5 to 5.2 ± 1.0 days), with lower 30-day readmission rates and improved pain management. Opioid consumption and major complications, including surgical site infections and thromboembolic events, were significantly reduced. Conclusion: Enhanced surgical and anesthetic techniques improve recovery, reduce complications, and lower healthcare costs. Findings support the broader implementation of robotic-assisted surgery and multimodal anesthesia to enhance perioperative care and surgical outcomes. Keywords: Comparative study, enhanced surgical techniques, multimodal anesthesia, perioperative outcomes, robotic-assisted surgery, complication rates.